The effect of disinfectant solutions on the hardness of acrylic resin denture teeth - Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, E. T.; Teraoka, M. T. (Blackwell Publishing, 2003)
This investigation studied the effects of disinfectant solutions on the hardness of acrylic resin denture teeth. The occlusal surfaces of 64 resin denture teeth were ground flat with abrasives up to 400-grit silicon carbide paper. Measurements were made after polishing and after the specimens were stored in water at 37 degreesC for 48 h. The specimens were then divided into four groups and immersed in chemical disinfectants (4% chlorhexidine; 1% sodium hypochlorite and sodium perborate) for 10 min. The disinfection methods were performed twice to simulate clinical conditions and hardness measurements were made. Specimens tested as controls were immersed in water during the same disinfection time. Eight specimens were produced for each group. After desinfection procedures, testing of hardness was also performed after the samples were stored at 37 degreesC for 7, 30, 60, 90 and 120 days. Data were analysed using two-way analysis of variance (anova) and Tukey's test at 95% confidence level. According to the results, no significant differences were found between materials and immersion solutions (P > 0.05). However, a continuous decrease in hardness was noticed after ageing (P < 0.05). It was conclude that the surfaces of both acrylic resin denture teeth softened upon immersion in water regardless the disinfecting solution.
Keywords: disinfection; hardness; denture teeth; removable prosthodontics; cross infection